(untitled) (Proceedings of Southern Federal University. Philology, 2020)
The article is devoted to the description of the lexical-textual simulator «word-concept-image» as a methodological tool that allows to identify adequately the axiological potential of the text and provide a deep understanding of publicistic works. The logic of textual activity with the use of a simulator focused on understanding publicism is described. The algorithm of textual activity is illustrated on a specific example: the analysis of the essay. Key words: axiological approach, teaching the Russian language, axiological potential, publicistic text, understanding of the text, linguoculturological characteristic of the text, lexical and textual simulator, methodological tools. DOI 10.18522/1995-0640-2020-4-184-192